(untitled) (Research, Society and Development, 2020)
The root canal therapy consists of phases aimed at cleaning and disinfection of the root canal system. The chemomechanical preparation is the one that makes use of instruments that can be used by means of mechanized techniques (rotary and reciprocation) and manual. The present study seeks to compare the three instrumentation techniques, based on cost and outcome, using the cost – minimization analysis in the perspective of the Social Service of Commerce (SESC - Brazil), and a time horizon of 10 years. The effectiveness of the techniques were raised through literature review and selection of systematic review studies. The costs were measured by the microcosting technique, in addition to the information from the SESC databases. In the analyzed period, the study shows that the use of the rotary system can increase the capacity of care by 44,67%, while the reciprocation system by 168 %. The financial impact would be R 103,683.87 and R 735,179.46 for the rotary and reciprocation, respectively. Using as reference the conventional technique, R 44.58 more is spent for the treatment with rotary instruments and R 84,03 for the reciprocation. Even with the highest allocating efficiency for the reciprocating technique with much greater coverage, the budget impact needs to be analyzed with caution. The incorporation of reciprocating technology demonstrating to be the technique with the highest allocating efficiency, best minimization cost ratio and reasonable cost of additional treatment in relation to other techniques.